Effects of shielding on pelvic and abdominal IORT dose distributions. Issue 11 (November 2016) - Esposito, Alessandro; Sakellaris, Taxiarchis; Limede, Patrícia; Costa, Filipa; Cunha, Luis T.; Dias, Anabela Gregório; Lencart, Joana; Sarmento, Sandra; Rosa, Carla Carmelo
Highlights: Impact of shielding elements in Intra-Operative Radiation Therapy (IORT). IORT system with shielding elements modeled with BEAMnrc and EGS++. Simulation of bone-like layer embedded in water phantom. Shielding efficiency improvement by optimization of irradiation geometry. Abstract: Purpose: To study the impact of shielding elements in the proximity of Intra-Operative Radiation Therapy (IORT) irradiation fields, and to generate graphical and quantitative information to assist radiation oncologists in the design of optimal shielding during pelvic and abdominal IORT. Method: An IORT system was modeled with BEAMnrc and EGS++ Monte Carlo codes. The model was validated in reference conditions by gamma index analysis against an experimental data set of different beam energies, applicator diameters, and bevel angles. The reliability of the IORT model was further tested considering shielding layers inserted in the radiation beam. Further simulations were performed introducing a bone-like layer embedded in the water phantom. The dose distributions were calculated as 3D dose maps. Results: The analysis of the resulting 2D dose maps parallel to the clinical axis shows that the bevel angle of the applicator and its position relative to the shielding have a major influence on the dose distribution. When insufficient shielding is used, a hotspot nearby the shield appears near the surface. At greater depths, lateral scatter limits the dose reduction attainable with shielding, although the presence of bone-like structures in the phantom reduces the impact of this effect. Conclusions: Dose distributions in shielded IORT procedures are affected by distinct contributions when considering the regions near the shielding and deeper in tissue: insufficient shielding may lead to residual dose and hotspots, and the scattering effects may enlarge the beam in depth. These effects must be carefully considered when planning an IORT treatment with shielding.